Islamic Economy: Buying And Selling, Syirkah, Rahn And Agreement Of Agreements - Dwi Apriliana; Budi Jaya Putra (Islamic Studies in the World, 2024)
Background. Islamic economy is grounded in principles derived from Islamic teachings, which emphasize ethical practices in economic transactions. The core aspects of Islamic economics include guidelines for buying and selling, partnerships (syirkah), collateral (rahn), and the formulation of agreements (aqd). These principles aim to promote fairness, justice, and transparency in trade and financial activities. However, the modern application of these principles remains a subject of debate, especially as it intersects with contemporary economic systems and financial practices. Purpose. This study aims to explore the Islamic economic principles related to buying and selling, syirkah, rahn, and agreements, analyzing their application in modern economies. It also seeks to examine the potential challenges and opportunities that arise when these principles are applied in today’s financial and business environments. Method. This research employs a qualitative approach, reviewing Islamic jurisprudence (fiqh) related to economic transactions and agreements. Data is gathered through literature reviews, case studies, and interviews with Islamic scholars and practitioners in the field of Islamic finance. Results. The findings suggest that while Islamic economic principles provide a solid ethical framework for business practices, there are challenges in adapting these principles to contemporary markets, particularly regarding interest-based transactions and the regulation of modern financial institutions. Syirkah and rahn are found to be effective tools for promoting fairness, but their implementation requires careful attention to Islamic legal requirements. Conclusion. The study concludes that the Islamic economic system offers valuable principles for ethical business practices but faces challenges in its full implementation within modern economic systems. Further efforts are needed to bridge the gap between Islamic finance principles and contemporary economic practices.